The Effect of Audit Fee, Audit Tenure, Audit Rotation and Client Company Size on Audit Quality (Empirical Study on Banking Sector Listed on Indonesia Stock Exchange (IDX) 2017-2019 Period) - Setiyaningsih, Eka; Sasongko, Noer (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The Effect of Audit Fee, Audit Tenure, Audit Rotation and Client Company Size on Audit Quality (Empirical Study on Banking Sector Listed on Indonesia Stock Exchange (IDX) 2017-2019 Period). This study aims to determine the effect of audit fees, audit tenure, audit rotation and client company size on audit quality. The population of this study is the Banking Sector Listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The sampling technique used purposive sampling, the type of data used was secondary data and obtained 26 banking sectors which were used as samples. This type of research uses a descriptive quantitative approach, which is measured using logistic regression analysis method with IBM Statistical Package for Social Sciences (SPSS) version 23. The results of this study indicate that: Audit Fee has no effect on Audit Quality. Audit Tenure has no effect on Audit Quality. Audit rotation has an effect on Audit Quality. The size of the Client's company affects the quality of the audit.